Makna Pembacaan Surah al-Fa>tihah pada Fenomena Ritual Jemaah Dzikrul Ghafilin di Desa Baron Nganjuk: Analisis Fenomenologi Alfred Schutz - Wachid, Mohamad Ibnu; Ahmadi, Rizqa (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2021)
AbstractThe recitation of surah al-Fatihah 100 times is a characteristic of the tradition of Jemaah Dzikrul Ghafilin. Normatively the recitation of al-Fatihah has various virtues including the master surah of the Qur'an, being a condition of the validity of prayer, used as a healing medicine. According to the provisional argument Dzikrul Ghafilin in general his orientation is purely to draw closer to Allah. In the meaning of the congregation in Baron Nganjuk is more oriented to the hope of the granting of all hajat. He is facilitated in work, education, healing, homemaking, and all things world. This research is considered important to dig deeper into the motives of pilgrims, more precisely how the understanding of pilgrims about Dzikrul Ghafilin in Baron Nganjuk, and how the findings are phenomenological. This research is qualitatively designed, using phenomenological methods and refers to the analysis of alfred schultz's construction of meaning. As for data collection techniques, the author directly observes as well as becomes a participant, conducts interviews and collects documentation. Phenomenologically the findings of this field study are; Theological motives add faith to Allah SWT, motives to preserve the teachings of the single mursyid Dzikrul Ghafilin (Gus Miek) in order to get the blessings of Gus Miek's teachings by facilitated all worship, and the motive of self-introspection in order to become a pious person in life. The interaction of the experience of the congregation is to get the support of the new family of Dzikrul Ghafilin pilgrims, gain insight into knowledge by exchanging opinions on life issues, and mutual tolerance to help the Dzikrul Ghafilin event. AbstrakPembacaan surah al-Fatihah 100 kali ialah ciri khas tradisi Jemaah Dzikrul Ghafilin. Secara normatif pembacaan al-Fatihah memiliki berbagai keutamaan diantaranya ialah surah induk al-Quran, menjadi syarat sahnya salat, dijadikan obat penyembuh. Menurut argumen sementara Dzikrul Ghafilin secara umum orientasinya ialah murni untuk mendekatkan diri kepada Allah. Dalam pemaknaan jemaah di Baron Nganjuk ini lebih berorientasi pada pengharapan terkabulnya segala hajat. Diataranya diperlancar dalam pekerjaan, pendidikan, kesembuhan, berumahtangga, dan segala perkara dunia. Penelitian ini dirasa penting untuk menggali lebih dalam motif jemaah, lebih tepatnya bagaimana pemahaman jemaah mengenai Dzikrul Ghafilin di Baron Nganjuk, beserta bagaimana hasil temuanya secara fenomenologis. Penelitian ini berdesain kualitatif, menggunakan metode fenomenologi dan mengacu analisis konstruksi makna Alfred Schultz. Adapun teknik pengumpulan data, penulis secara langsung melakukan observasi sekaligus menjadi partisipan, melakukan wawancara dan mengumpulkan dokumentasi. Secara fenomenologis hasil temuan dari penelitian lapangan ini ialah; Motif Teologis menambah keimanan kepada Allah SWT, motif melestarikan ajaran mursyid tunggal Dzikrul Ghafilin (Gus Miek) agar mendapatkan berkah ajaran Gus Miek dengan diperlancar segala hajat, dan motif intropeksi diri agar menjadi pribadi umat yang saleh dalam kehidupan. Interaksi pengalaman jemaah ialah mendapat dukungan keluarga baru jemaah Dzikrul Ghafilin, mendapatkan wawasan ilmu dengan saling bertukar pendapat masalah kehidupan, dan saling toleransi membantu acara Dzikrul Ghafilin.Kata Kunci: al-Fatihah; Dzikrul Ghafilin; Fenomenologi.